2014
DOI: 10.1155/2014/845308
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Hearing Screening and Early Diagnostic in the NICU

Abstract: The aim was to describe the outcome of neonatal hearing screening (NHS) and audiological diagnosis in neonates in the NICU. The sample was divided into Group I: neonates who underwent NHS in one step and Group II: neonates who underwent a test and retest NHS. NHS procedure was automated auditory brainstem response. NHS was performed in 82.1% of surviving neonates. For GI, referral rate was 18.6% and false-positive was 62.2% (normal hearing in the diagnostic stage). In GII, with retest, referral rate dropped to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 32 publications
5
41
2
6
Order By: Relevance
“…These three above studies seemed to that higher referral rate in NICU than us were observed in developed and developing countries. The more reasonable lower referral rate in our NICU study could be attributed to be a little late time set for hearing screening when infants were transferred to NBC with an average time of 13 Days, speculated to be late than the above three studies[ 17 19 ]. The second probable reason for lower referral rate in our NICU group could be attributed to our hearing screener with well experienced (> 10 years work) full-time nursery background.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…These three above studies seemed to that higher referral rate in NICU than us were observed in developed and developing countries. The more reasonable lower referral rate in our NICU study could be attributed to be a little late time set for hearing screening when infants were transferred to NBC with an average time of 13 Days, speculated to be late than the above three studies[ 17 19 ]. The second probable reason for lower referral rate in our NICU group could be attributed to our hearing screener with well experienced (> 10 years work) full-time nursery background.…”
Section: Discussionmentioning
confidence: 81%
“…Our 2.8% referral rate was also much lower than 9.2% by van Dommelen [ 18 ] NICU study in Dutch, in which their refer rate was 9.2%(2933/32038) using AABR and 95.8% of infants were screened < 1 months, but without mention of its average screening time. Additionally, in one Brazil study[ 19 ], their refer rate was 4.1% using after twice AABR screening without statement of its average screening time. These three above studies seemed to that higher referral rate in NICU than us were observed in developed and developing countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the brainstorming session, modifications were not suggested to ten items (2,3,4,7,12,14,20,21, 27 and 31), while the modifications deemed necessary for 25 items. Items that were the most commented by the parents guided the discussion among experts.…”
Section: Establishment Of Alterations By Item From the Notes Of Parementioning
confidence: 99%
“…Several instruments address the issue of factors that determine auditory and language skills (1,2,3) , many of them individualizing the perception of the family in relation to the child's language development (4,5,6) . The issue of therapeutic fit with infants has also been discussed.…”
Section: Introductionmentioning
confidence: 99%